2019
DOI: 10.1038/s41388-019-1047-4
|View full text |Cite
|
Sign up to set email alerts
|

Targeting chemoresistant colorectal cancer via systemic administration of a BMP7 variant

Abstract: Despite intense research and clinical efforts, patients affected by advanced colorectal cancer (CRC) have still a poor prognosis. The discovery of colorectal (CR) cancer stem cell (CSC) as the cell compartment responsible for tumor initiation and propagation may provide new opportunities for the development of new therapeutic strategies. Given the reduced sensitivity of CR-CSCs to chemotherapy and the ability of bone morphogenetic proteins (BMP) to promote colonic stem cell differentiation, we aimed to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…Several approaches of differentiation pathway targeting were reported 9 . There are usage of signaling molecules, such as retinoic acid (RA) 7 , cAMP 10 , retinoids 11 , peroxisome proliferator-activated receptor—γ (PPARγ) antagonist 12 , PTPRK-RSPO3 function-blocking antibodies 13 , inhibition of IDH1 in IDH1-mutant tumors 14 , inhibition of aurora kinase 15 , epigenetic modulators of Bromodomain-containing protein 4 (BRD4i) 16 , administration of bone morphogenetic proteins 17 , such as enhanced variant of BMP7 18 and inhibition of histone deacetylase (HDAC). A number of HDAC inhibitors were evaluated in clinical trials and some of them such as vorinostat (SAHA), romidepsin (depsipeptide) and belinostat (PXD-101) have been approved for therapy of blood cancers by the US Food and Drug Administration (FDA) 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Several approaches of differentiation pathway targeting were reported 9 . There are usage of signaling molecules, such as retinoic acid (RA) 7 , cAMP 10 , retinoids 11 , peroxisome proliferator-activated receptor—γ (PPARγ) antagonist 12 , PTPRK-RSPO3 function-blocking antibodies 13 , inhibition of IDH1 in IDH1-mutant tumors 14 , inhibition of aurora kinase 15 , epigenetic modulators of Bromodomain-containing protein 4 (BRD4i) 16 , administration of bone morphogenetic proteins 17 , such as enhanced variant of BMP7 18 and inhibition of histone deacetylase (HDAC). A number of HDAC inhibitors were evaluated in clinical trials and some of them such as vorinostat (SAHA), romidepsin (depsipeptide) and belinostat (PXD-101) have been approved for therapy of blood cancers by the US Food and Drug Administration (FDA) 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Cells were treated with 10 μM GANT61 (ENZO Lifesciences), and equimolar concentration of Oxaliplatin (Selleckchem) and 5-Fluorouracil (5-FU) (Selleckchem) as described earlier 41 . In detail, to avoid precipitation of the combined Oxaliplatin and 5-FU, we administered 5-FU three hours after Oxaliplatin.…”
Section: Methodsmentioning
confidence: 99%
“…In preclinical studies, treatment with WNT/bcatenin inhibitors, iLGK974, Wnt-C59, and cyclosporin A, impaired CSC survival in different cancer types (129)(130)(131). In this context, we have recently demonstrated that the use of a variant of BMP7 with enhanced stability (BMP7v) induced the differentiation of CD44v6 + cells, suppressed Wnt pathway activity and sensitized CSCs to standard and target therapies (132). Recently, we demonstrated that cytokines secreted by CAFs boosted resistance to PI3K/AKT inhibitors in colorectal CSCs and this protective effect was overcome by the triple targeting of Her2, PI3K and MEK (103).…”
Section: Caf Role In Inducing Csc-mediated Resistance To Therapymentioning
confidence: 99%